2009
DOI: 10.1186/bf03353162
|View full text |Cite
|
Sign up to set email alerts
|

Possible influence of ultra-fast Kelvin wave on the equatorial ionosphere evening uplifting

Abstract: Equatorial 3.5-day ultra-fast Kelvin wave was observed in the MLT zonal wind measured by meteor radar at Cariri (7.4• S, 36.5• W, geomag. 8• S) and in the stratosphere-mesosphere temperature structures from the TIMED/SABER data. The ionospheric F-layer bottom-side virtual height h F and the critical frequency f o F 2 observed at Fortaleza (3.9• S, 38.4• W, geomag. 5 • S) also showed similar oscillation structures, indicating an influence of the Kelvin wave in the F region height and modulation of E × B uplifti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
3
21
0
Order By: Relevance
“…This approximation is necessary in this present study because we do not know the UFK wave amplitudes at the E-region dynamo altitudes. In the TIMED/SABER temperature UFK oscillations, Takahashi et al (2009) found an amplitude of 5 K at 80 km, and an amplitude of 10 K at 120 km. This indicates that the wave amplitude increased with height by a factor of 2 from the 40 km height range.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This approximation is necessary in this present study because we do not know the UFK wave amplitudes at the E-region dynamo altitudes. In the TIMED/SABER temperature UFK oscillations, Takahashi et al (2009) found an amplitude of 5 K at 80 km, and an amplitude of 10 K at 120 km. This indicates that the wave amplitude increased with height by a factor of 2 from the 40 km height range.…”
Section: Methodsmentioning
confidence: 99%
“…According to Takahashi et al (2009), the UFK waves can play an important role over the equatorial ionosphere through dynamo effects. The zonal wind in the lower thermosphere could be one of the principal causes of the day-to-day variability in h F. The UFK waves can superimpose onto, and/or modulate the tidal winds (mainly the zonal component), resulting in an electron density variation of the E-layer by the E-region dynamo.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations